1985
DOI: 10.1128/aem.49.6.1467-1471.1985
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory infection of chicken eggs with Campylobacter jejuni by using temperature or pressure differentials

Abstract: Fertile chicken eggs were infected in our laboratory with Campylobacter jejuni suspensions by using temperature or pressure differential methods of inoculation. After 2 days of incubation, over 90% of the eggs carried C. jejuni when iron was present in the inoculum. This percentage declined rapidly until by day 8, less than 10% of the eggs were detectably infected. However, up to 11% of hatched, healthy chicks carried C. jejuni in their intestinal tracts. The isolated organisms were of the same serotype as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our preliminary studies indicated that C. jejuni was able to survive up to 2 weeks in eggs with or without anti-Campylobacter antibody kept at 18°C after artificial injection into the egg yolk (Sahin et al, 2001b), which is in contrast to the short survival rate of the organism at low temperatures in vitro (Solomon and Hoover, 1999;Jacobs-Reitsma, 2000). Thus, these observations (Clark and Bueschkens, 1985;Shanker et al, 1986;Sahin et al, 2001b) plus a recent finding that 'viable but not culturable' forms of C. jejuni could be resuscitated by injection into the yolk sac of embryonated eggs (Cappelier et al, 1999) indicate that, once C. jejuni enters inside the egg, it can survive there long enough to potentially infect the hatchlings. The ability of C. jejuni to survive in egg yolk, even in the presence of high levels of Campylobacter-specific antibody, for a long time is probably related to lack of complement in the yolk.…”
Section: Vertical Transmissionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our preliminary studies indicated that C. jejuni was able to survive up to 2 weeks in eggs with or without anti-Campylobacter antibody kept at 18°C after artificial injection into the egg yolk (Sahin et al, 2001b), which is in contrast to the short survival rate of the organism at low temperatures in vitro (Solomon and Hoover, 1999;Jacobs-Reitsma, 2000). Thus, these observations (Clark and Bueschkens, 1985;Shanker et al, 1986;Sahin et al, 2001b) plus a recent finding that 'viable but not culturable' forms of C. jejuni could be resuscitated by injection into the yolk sac of embryonated eggs (Cappelier et al, 1999) indicate that, once C. jejuni enters inside the egg, it can survive there long enough to potentially infect the hatchlings. The ability of C. jejuni to survive in egg yolk, even in the presence of high levels of Campylobacter-specific antibody, for a long time is probably related to lack of complement in the yolk.…”
Section: Vertical Transmissionmentioning
confidence: 91%
“…Shane et al (1986) isolated the organism from both the interior surface of the eggshell and the egg contents after swabbing feces containing C. jejuni onto the surface of the eggs. Following experimental infections of eggs with C. jejuni by either the temperature differential method (Clark and Bueschkens, 1985) or inoculation of egg albumen via direct injection (Shanker et al, 1986), the organism was recovered from both the contents of unhatched eggs and from the newly hatched chicks. Our preliminary studies indicated that C. jejuni was able to survive up to 2 weeks in eggs with or without anti-Campylobacter antibody kept at 18°C after artificial injection into the egg yolk (Sahin et al, 2001b), which is in contrast to the short survival rate of the organism at low temperatures in vitro (Solomon and Hoover, 1999;Jacobs-Reitsma, 2000).…”
Section: Vertical Transmissionmentioning
confidence: 99%
“…If natural infection of egg contents occurs, it probably is primarily a consequence of fecal contamination of the egg shell surface and penetration via egg shell and egg shell cracks, as intact egg shells appear to be permeable to C. jejuni (Clark and Bueschkens ; Sahin and others ). Given that the eggs are infected, the question remains whether this generates colonized chicks and Campylobacter ‐positive flocks (King and others ).…”
Section: Risk Factors For Campylobacter Infection and External Contammentioning
confidence: 99%
“…The ability of C. jejuni to penetrate the eggshell and also outer and inner eggshell membranes was investigated by using a temperature‐differential process as described previously with minor modifications (Clark and Bueschkens 1985). This method works based on the assumption that a warm egg contracts while cooling, and the resultant negative pressure can draw bacteria into/through the eggshell.…”
Section: Experimental Egg Penetration Studiesmentioning
confidence: 99%
“…(1986) isolated the organism from both interior surface of egg shell and egg contents after swabbing faeces containing C. jejuni onto the egg surface. Following experimental infection of eggs with C. jejuni by either temperature differential method (Clark and Bueschkens 1985) or inoculation of egg albumen via direct injection (Shanker et al. 1986), the organism was recovered from both the contents of unhatched eggs and from the newly hatched chicks.…”
Section: Introductionmentioning
confidence: 99%